La proteins from Drosophila melanogaster and Saccharomyces cerevisiae: a yeast homolog of the La autoantigen is dispensable for growth. - Yoo, C.J.; Wolin, S.L. (Molecular and Cellular Biology, 1994)
The human autoantigen La is a 50-kDa protein which binds to the 3' termini of virtually all nascent polymerase III transcripts. Experiments with mammalian transcription extracts have led to the proposal that the La protein is required for multiple rounds of transcription by RNA polymerase III (E. Gottlieb and J. A. Steitz, EMBO J. 8:851-861, 1989; R. J. Maraia, D. J. Kenan, and J. D. Keene, Mol. Cell. Biol. 14:2147-2158, 1994). Although La protein homologs have been identified in a variety of vertebrate species, the protein has not been identified in invertebrates. In order to begin a genetic analysis of La protein function, we have characterized homologs of the La protein in the fruit fly Drosophila melanogaster and the yeast Saccharomyces cerevisiae. We show that both the Drosophila and yeast La proteins are bound to precursors of polymerase III RNAs in vivo. The Drosophila and yeast proteins resemble the human La protein in their biochemical properties, as both proteins can be partially purified from cells by a procedure previously devised to purify the human protein. Similarly to vertebrate La proteins, the Drosophila and yeast homologs preferentially bind RNAs that terminate with a 3' hydroxyl. Despite the fact that the La protein is conserved between humans and Saccharomyces cerevisiae, yeast cells containing a null allele of the gene encoding the La protein are viable, suggesting that another protein(s) plays a functionally redundant role.